IDENTIFICATION OF FAULT CONTINUITY AND HOT WATER RESERVOIR USE SCHLUMBERGER CONFIGURATION RESISTIVITY METHOD IN CANGAR - Widyasandy, Dhony; Nugraha, Aulia K; Kurniawan, Husni Cahyadi; Luthfin, Ahmad (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2020)
Research that uses the Schlumberger configuration resistivity method had been conducted in Cangar. The purpose of this study is to identify cracks/faults and potential hot springs use resistivity well analysis and correlate it with rock lithology in Cangar, East Java. Data acquisition is carried out using 3 tracks with 10 sounding points. The space between points is 50 meters. The rock resistivity values obtained were 9945 Î©m, 7360 Î©m, and 5573 Î©m which were thought to be breccia layers and functioned as hot springs. This estimation is strengthened by the existence of a layer of breccia-andesite because this layer is very good as a water reservoir. In addition, based on the lateral cross-section on lane 1, there was a decrease in boulder-sized breccia-andesite layers; this decrease was the production of faults.